Pengembangan Sistem Informasi Kesehatan Gizi Pasien Berbasis Mobile (Studi Kasus: Klinik UB Malang) - Nadir Basalamah; Achmad Arwan; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Nutrition is an important component in the formation of various important elements in the human body such as tissue development, reproduction and the formation of energy for metabolism. Healthy and balanced nutrition can be obtained by visiting hospitals and clinics that provide nutrition poly services. Nutrition poly is a service that aims to serve patients to obtain healthy and optimal nutrition. Services in nutrition poly include recording a nutrition data, designing food menus, monitoring of evaluation result and nutrition consultation. Nutritional data recording services and food menu design are carried out conventionally so that access to patient nutrition data is limited and there is no mechanism for a schedule reminder to return to nutrition poly or meal schedules. This problem can be solved by developing a mobile-based nutrition information system that can be used by nutritionists in recording nutritional data and for patients in monitoring nutritional development. The system was developed with the waterfall methodology and uses technology in the form of the use of the Kotlin programming language to develop mobile applications with the Android operating system. This research stage begins with a system requirements analysis that results in 44 system functional requirements. After the requirements analysis is carried out, the next step is to carry out the design and implementation process of the system. After the design and implementation have been carried out, the next stage is testing which includes unit testing, integration testing and system testing. The results of the system testing that have been carried out produce a valid status with a value of 100%, namely the system developed in accordance with the design results.